Fast Clinical, but Long-Term, Biochemical Remission after Waterhouse–Friderichsen Syndrome - Igor Alexander Harsch (Case Reports in Endocrinology)
Background. The Waterhouse–Friderichsen Syndrome (WFS) is a course of bacterial meningitis with a lethality rate that is still high today. One hallmark of the clinical course is intravascular coagulopathy. This causes hemorrhagic infarctions in the adrenal glands, rapidly causing a primary adrenal insufficiency. Only few reports highlight the course of the remaining adrenal insufficiency or adrenal restitution in survivors. Case Presentation. After 3 weeks in an intensive care unit, a 45-year-old male survived WFS with necroses on the legs and forefeet and with primary adrenal insufficiency confirmed by the ACTH stimulation test. The substitution therapy with hydrocortisone and fludrocortisone could be gradually discontinued after nine months due to a further positive clinical course. Although the patient reported good mental and physical performance further on, the cortisol response in ACTH testing showed tiny incremental rises of the stimulated serum cortisol, but to reach a formally normal level, it took about five years. Discussion. The report demonstrates a case with a relatively fast clinical remission. A remission of the corticotrophic response occurred in small increments during an observational period of five years. The data suggest that not only a clinical remission is possible but also a complete biochemical remission, although this process may take a much longer timespan.